Comparison of Ozonation and Electro-Fenton Processes for Sodium Azide Removal in Medical Laboratory Wastewater by Using Central Composite Design. Issue 17 (22nd November 2021) - Basturk, Irfan; Murat-Hocaoglu, Selda; Varank, Gamze; Yazici-Guvenc, Senem
ABSTRACT: This study aims to analyze sodium azide removal from medical laboratory wastewater by using Electro-Fenton (EF) and ozonation methods and to determine the optimum process conditions. Under optimum conditions; 98.9% and 99.6% sodium azide removal efficiency was obtained through EF and ozonation processes, respectively. This is the first and the only optimization study in literature in which response surface methodology and central composite design were used for sodium azide removal from wastewater. Results of the study indicated that EF and ozonation processes are effective methods for sodium azide removal, and central composite design is a suitable tool for process optimization.